2018
DOI: 10.1017/s0954579418000925
|View full text |Cite
|
Sign up to set email alerts
|

Parenting, culture, and the development of externalizing behaviors from age 7 to 14 in nine countries

Abstract: Using multilevel models, we examined mother-, father-, and child-reported (N = 1,336 families) externalizing behavior problem trajectories from age 7 to 14 in nine countries (China, Colombia, Italy, Jordan, Kenya, the Philippines, Sweden, Thailand, and the United States). The intercept and slope of children's externalizing behavior trajectories varied both across individuals within culture and across cultures, and the variance was larger at the individual level than at the culture level. Mothers' and children'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 101 publications
3
48
0
Order By: Relevance
“…On the other hand, the child’s externalizing behavior problem was associated with the parent’s PTSD symptom only in the cross-sectional setting (both in 2012 and 2014), suggesting that externalizing symptoms was more responsive to parents’ current level of stress. The reason why the cross-sectional relationships were getting more robust in 2014 than 2012 could be supported by the developmental theory (43), which refers that the risks of developing the externalizing behavior problem are higher at the middle childhood to adolescence than the infant. Because the age of the targeted children of the current study was started at range 4 to 6 years (i.e., infant), it could be expected that those association is getting stronger along with their development, year by year.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the child’s externalizing behavior problem was associated with the parent’s PTSD symptom only in the cross-sectional setting (both in 2012 and 2014), suggesting that externalizing symptoms was more responsive to parents’ current level of stress. The reason why the cross-sectional relationships were getting more robust in 2014 than 2012 could be supported by the developmental theory (43), which refers that the risks of developing the externalizing behavior problem are higher at the middle childhood to adolescence than the infant. Because the age of the targeted children of the current study was started at range 4 to 6 years (i.e., infant), it could be expected that those association is getting stronger along with their development, year by year.…”
Section: Discussionmentioning
confidence: 99%
“…Lansford and colleagues (2018) investigated parenting, culture, and the development of externalizing behaviors in nine countries, including China, Colombia, Italy, Jordan, Kenya, the Philippines, Sweden, Thailand, and the United States. They examined mother-, father-, and child-reported ( N = 1,336 families) externalizing behavior problem trajectories from age 7 to 14.…”
Section: Understanding Cultural Differences and Similarities In Develmentioning
confidence: 99%
“…Several studies have shown that one out of four people in the world develop mental health problems at some point in their life [ 1 ]. Adolescence is a key period during which the incidence of externalizing and internalizing problems increases significantly [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%